(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The twenty-first century has brought significant changes to education, requiring learners to acquire not only subject knowledge but also a range of skills necessary for success in an increasingly interconnected and technology-driven world. English language instruction plays a crucial role in developing these competencies by providing opportunities for communication, collaboration, creativity, critical thinking, and digital literacy. Modern English language classrooms have evolved from traditional grammar-focused environments into dynamic learning spaces where students actively engage in problem-solving, teamwork, and authentic communication. This article explores how English language instruction contributes to the development of 21st-century skills and examines the importance of integrating these competencies into language education.